Color Emotion Based on CNCS Color System (Journal of Fiber Bioengineering and Informatics, 2016)
In this study, color emotion based on CNCS color system was investigated. The research included singlecolor preference and multi-color coordination emotion. Six themes of International Textile color tradedwere selected as color samples. At the first step, forty-two single colors were regarded as color samplesfor color preference survey. At the second step, twenty-four kinds of color coordination were madeaccording to six color concepts, and color emotion survey for multi-color coordination was conducted. Inthe second part, fifteen color emotion scales such as “modern-classic”, “formal-casual”, “gaudy-tasteful”,“lively-stiff”, “intellectual-nonintellectual”, “like-dislike” and so on were selected according to SemanticDifferential Method. The survey was conducted among the undergraduate college students from Xi'anPolytechnic University. Color histogram was used to express the result of single color preference. It wasclear that the popularity of these released colors was not average and the more favorite colors were palechromatic colors. Factor Analysis and cluster analysis were used to conduct the data from the secondpart survey. Three factors were extracted and labeled “personality”, “taste”, and “fashion”. Twenty-four multi-color combinations were classified into three groups. It indicated that the comprehensive coloremotion was more important than other factors.
Keywords: Color Preference; Color Emotion; Multi-color Combination; Semantic Differential Method; Factor Analysis